Global bibliometric analysis of traditional Chinese medicine regulating gut microbiota in the treatment of diabetes from 2004 to 2024 - Liang, Jieling; Lin, Xiaojuan; Liao, Xin; Chen, Xi; Zhou, Ying; Zhang, Lin; Qin, Yunyun; Meng, Haoru; Feng, Zhongwen (Frontiers in Pharmacology, 2025)
ObjectivesThe therapeutic efficacy of Traditional Chinese Medicine (TCM) in modulating gut microbiota for diabetes treatment has garnered increasing scholarly attention. This study aims to meticulously examine current research trajectories and focal areas from 2004 to 2024, providing a foundational framework for future inquiries.MethodsA comprehensive search of documents published between 2004 and 2024 was conducted using the Web of Science database. The resulting data were analyzed and visualized using R software, VOSviewer, and CiteSpace.ResultsThe study included a total of 751 documents. From 2004 to 2022, the number of annual publications showed a continuous upward trend (2004: n = 1 to 2022: n = 159), and the number of publications in 2023 (n = 141) decreased slightly from the previous year. China emerged as the leading country in terms of article publications (n = 430). Additionally, the United States played a prominent role in international research collaborations. Frontiers in Pharmacology (n = 31) was the most frequently published journal, while Nature (n = 1,147) achieved the highest citation count. Key identified keywords included obesity, insulin resistance, inflammation, and oxidative stress.ConclusionThree key research focuses in this domain include: the therapeutic effects of active constituents in TCM on diabetes via gut microbiota modulation, the underlying mechanisms through which TCM influences gut microbiota in diabetes management, and the targeted regulation of specific gut bacterial populations by TCM in the treatment of diabetes.